Seeing Time - Sabolius, Kristupas (Religija ir kultūra, 2010)
By analyzing the texts of Kant and Heidegger and juxtaposing them with the concrete practices of exercising “empty space” and “empty time without things or events” (such as the prolonged observation of Malevich’s ‘Black Square’), this paper aims to reveal the suppressed but essential role of imagination in the transcendental structures of perception. Imagination is not to be considered a subjective faculty, activating inner visions and secondary, i. e. reproductive creativity. On the contrary, being ontologically primary as exibitio originaria, the force enabling seeing and schematizing the perception, it freely constructs the universal horizon of time. And namely due to the fundamental property of imagination to be linked with change and flux, one can find an opening of transcendental solipsism to the reality which is the movement itself.